2017
DOI: 10.1002/hed.24824
|View full text |Cite
|
Sign up to set email alerts
|

Impact of positive margins on outcomes of oropharyngeal squamous cell carcinoma according to p16 status

Abstract: Patients with p16-positive oropharyngeal SCC and positive margins after excision maintain a low risk of recurrence despite most receiving RT alone as adjuvant treatment. These findings raise questions regarding the additional benefit of postoperative CRT in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 24 publications
(51 reference statements)
0
34
2
2
Order By: Relevance
“…Although these patients are more likely to receive RT and/or CT, we found that positive surgical margins were independently associated with decreased OS for all subsites, reinforcing the importance of complete surgical extirpation. This has been replicated at many other head and neck sites . The patient and tumor factors found here can be used to identify patients at high risk of positive margins, and these patients should be referred to high‐volume facilities in order to maximize the chance of achieving negative margins and, accordingly, their OS.…”
Section: Discussionmentioning
confidence: 71%
“…Although these patients are more likely to receive RT and/or CT, we found that positive surgical margins were independently associated with decreased OS for all subsites, reinforcing the importance of complete surgical extirpation. This has been replicated at many other head and neck sites . The patient and tumor factors found here can be used to identify patients at high risk of positive margins, and these patients should be referred to high‐volume facilities in order to maximize the chance of achieving negative margins and, accordingly, their OS.…”
Section: Discussionmentioning
confidence: 71%
“…The overall positive margin rate of 31% identified here is consistent with other studies on parotid tumors, but markedly higher than with most other types of HNC. 16,[25][26][27][28][29][30][31] The parotid gland is near multiple critical structures, particularly the facial nerve; therefore, wide resection margins may be deprioritized to reduce surgical morbidity. 10 Advanced T stage was associated with positive margins, with 50% of T4A tumors with positive margins compared to 18% of T1.…”
Section: Discussionmentioning
confidence: 99%
“…A similar thought process has recently been examined with regard to breast cancer for focally positive margins . Within the head and neck, the necessity for addition of chemotherapy in the presence of positive margins has also been questioned for p16‐positive oropharyngeal cancer . At present, however, this rationale does not seem to have been explored in a systematic manner for other disease sites within the head and neck.…”
Section: Discussionmentioning
confidence: 99%